2015
DOI: 10.1042/cs20140826
|View full text |Cite
|
Sign up to set email alerts
|

SRY gene transferred by extracellular vesicles accelerates atherosclerosis by promotion of leucocyte adherence to endothelial cells

Abstract: We set out to investigate whether and how SRY (sex-determining region, Y) DNAs in plasma EVs (extracellular vesicles) is involved in the pathogenesis of atherosclerosis. PCR and gene sequencing found the SRY gene fragment in plasma EVs from male, but not female, patients; EVs from male patients with CAD (coronary artery disease) had a higher SRY GCN (gene copy number) than healthy subjects. Additional studies found that leucocytes, the major source of plasma EVs, had higher SRY GCN and mRNA and protein express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…showing that SRY (sex-determining region, Y) DNAs in plasma EV from coronary artery disease patients was increased. The authors concluded that EV-associated genomic DNA can be transferred to and expressed in recipient cells, thus influencing the function of the recipient cells by increasing DNA-coding mRNA and protein levels [ 39 ]. These in vivo results together with our in vitro data show that horizontal DNA transfer seems to be a rare but physiological process.…”
Section: Discussionmentioning
confidence: 99%
“…showing that SRY (sex-determining region, Y) DNAs in plasma EV from coronary artery disease patients was increased. The authors concluded that EV-associated genomic DNA can be transferred to and expressed in recipient cells, thus influencing the function of the recipient cells by increasing DNA-coding mRNA and protein levels [ 39 ]. These in vivo results together with our in vitro data show that horizontal DNA transfer seems to be a rare but physiological process.…”
Section: Discussionmentioning
confidence: 99%
“…61,167 DNA Although evidence that EVs contain DNA is scant in literature when compared with EV-RNA, an increasing number of studies suggests that under stress, cells release EVs containing DNA that differs from DNA present in apoptotic bodies. [168][169][170][171] As in RNA analysis, next-generation sequencing, PCR, and other methods can be used to analyze or validate the EV-DNA content. Moreover, a DNAse digestion step of intact EVs is needed to demonstrate the presence of intravesicular DNA.…”
Section: Considerations and Recommendationsmentioning
confidence: 99%
“…The SRY gene-enriched extracellular vesicles contributed to enhanced adherence of monocytes and endothelial cells. In addition, injection of SRY extracellular vesicles into ApoE −/− mice accelerated atherosclerosis, which suggested a potential pathophysiological role of the leukocyte-derived exosomes [40]. …”
Section: Role Of Exosomes In Vascular Diseasementioning
confidence: 99%